Os ajustes termorregulatórios induzidos pela estimulação colinérgica central durante o exercício físico são mediados pelo barorreflexo arterial - Washington Pires (2008)
The aim of this study was to evaluate if the effects of central cholinergic receptors stimulation on thermoregulation, in untrained rats during exercise, is mediated by arterial baroreceptors. The animals were anesthetized and fitted with cannulae into the lateral cerebral ventricle. The rats were allowed to recover from surgery and subsequently submitted to sinoaortic denervation (Sad) or sham surgery. After recovery the animals were submitted to a new surgical procedure, and a polyethylene catheter was implanted into the ascendant aorta and a thermal sensor into the abdominal cavity. On the day of experiments, tail skin temperature (Ttail), intraperitoneal temperature (Tb) and pulsatile arterial pressure were measured after the injection of 2 L of 10 × 103 M physostigmine (Phy) or 0.15 M NaCl solution (Sal) into the cerebral ventricle. During exercise, Phy-treated rats had a higher increase in mean blood pressure (139 2 mmHg Phy-sham vs 1243 mmHg Sal-sham; P<0.05) and higher Ttail (30,8 6 ºC Phy-sham vs 28,0 5 ºC Sal-sham; P<0.05). In addition, Phy injection attenuated the exercise-induced increase in heart rate (413 41 bpm Phy-sham vs 516 7 bpm Sal-sham; P<0.05) and Tb (37,9 0,6 ºC Phy-sham vs 38,61,0 ºC Sal-sham; P<0.05) compared with controls. In sinoaortic denervated rats Phy injection increase blood pressure (167 12 mmHg Phy-Sad vs 126 4 mmHg Sal-Sad), however heart rate, Ttail and Tb responses not were different compared Sal injection. We conclude that the termoregulatory adjustments induced by central cholinergic stimulation during exercise are mediate by arterial baroreflex.